1997
DOI: 10.1103/physreva.55.1945
|View full text |Cite
|
Sign up to set email alerts
|

Medium modification of two-particle scattering in nonideal Bose systems

Abstract: Medium modification of scattering properties in interacting Bose systems are considered by solving the Bethe-Salpeter equation. An equation of state for the normal phase (generalized Beth-Uhlenbeck formula) is given using the in-medium phase shifts to include two-particle correlations. Conclusions are drawn for systems of bosonic atoms with repulsive interaction such as sodium 23 Na and rubidium 87 Rb. It is shown that the in-medium scattering length and the absolute value of the in-medium scattering phase shi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…is linked to the scattering length by the small momentum expansion, p = k. From (8) we obtain [26] a = − π λ…”
Section: Many-body T-matrix Approximation and Bethe-salpeter Equmentioning
confidence: 99%
See 2 more Smart Citations
“…is linked to the scattering length by the small momentum expansion, p = k. From (8) we obtain [26] a = − π λ…”
Section: Many-body T-matrix Approximation and Bethe-salpeter Equmentioning
confidence: 99%
“…For further relations of the T-matrices in different dimensions see [30]. In [26] the expression (12) was discussed and it was found that this medium-dependent scattering length diverges at the Bose-Einstein transition characterized by the critical density and temperature. We will employ (12) as a good measure of approaching the Bose-Einstein condensate.…”
Section: Many-body T-matrix Approximation and Bethe-salpeter Equmentioning
confidence: 99%
See 1 more Smart Citation
“…We can observe [67] that the interaction is behaved such that the denominator vanishes itself when approaching the phase transition which means…”
Section: Phase Diagram Of Interacting Photonsmentioning
confidence: 98%
“…We will derive the medium-dependent scattering range from solving the Bethe-Salpeter equation which diverges near the phase transition. This method has been used before in [62,67] such that we might present it here only briefly. The Bethe-Salpeter equation for the many-body Tmatrix with a center-of-the-mass momentum K, and incoming and outgoing difference momenta p and p ′ of the two particles, respectively, can be solved…”
Section: Phase Diagram Of Interacting Photonsmentioning
confidence: 99%